Heat accelerates degradation of β-lactoglobulin fibrils at neutral pH. (March 2022) - Chen, Da; Pinho, Lorena Silva; Federici, Enrico; Zuo, Xiaobing; Ilavsky, Jan; Kuzmenko, Ivan; Yang, Zhi; Jones, Owen Griffith; Campanella, Osvaldo
Abstract: Fibrous aggregates of β -lactoglobulin display superior mechanical and interfacial properties compared to the native protein. These properties directly link to the protein morphology and structure. When incorporated into food matrices, during processing protein fibrils are exposed to pH shifts and high temperature conditions, which accelerate their degradation. In the present study, neutralized β -lactoglobulin fibrils were heated at 100 °C and 121 °C for various times to assess their degradation. Fibril morphology, structure, and viscosity in solution were examined by microscopy, scattering, spectroscopy, and rheology. Atomic force microscopy showed the contour length of the protein fibrils decreased gradually with heating at 100 °C and 121 °C, with greater decreases at 121 °C. Increased fibril diameters (∼15–25 nm) were observed at 121 °C for 5–15 min heating and were disrupted upon further heating. Small-angle x-ray scattering indicated an increase in fibril radius with heating at pH 7 followed by a decrease at prolonged heating, whereas fibril length decreased continuously with heating. Thioflavin T fluorescence, circular dichroism and Fourier transform infrared spectroscopy confirmed the conversion of β -sheet to random coils as fibrils were degraded during thermal treatment at pH 7. Surface hydrophobicity of fibrils decreased with increase in heating temperature and time, coinciding with an increase in the content of non-aggregated proteins. Viscosity of fibril solutions increased when fibrils were heated at 100 °C, whereas at 121 °C their viscosity first increased and then decreased. These findings imply heating at 100 °C and 121 °C facilitates degradation and depolymerisation of β -lactoglobulin fibrils with aggregation as an intermediate step. Graphical abstract: Image 1 Highlights: Heating at 100 °C and 121 °C degraded and depolymerized β -lactoglobulin fibrils. Heating at 121 °C for short times induced formation of thicker fibrils. Heating decreased fibril β -sheet structure and increased random coil. Surface hydrophobicity and viscosity of fibril solutions were altered by heating.